Fertility Desires of Adolescents and Young Adults Living in Large Families – The Role of the Family of Origin and the Cultural Stereotypes - Bálity, Csaba; Duráczky, Bálint (European Journal of Mental Health, 2017)
The Role of the Family of Origin and the Cultural Stereotypes: In our study, we aimed at examining the childbearing desires of adolescents and young adults living in Hungarian large families. Two different methods were used during the dyadic data analysis. On the one hand, correlation between the fertility desires of siblings, on the other hand, the absolute difference in the planned number of children was measured. The data indicate that in two out of the three dyads of siblings, created by the order of birth, significant correlation can be measured. Pseudo-dyads were created in order to test if the above mentioned parallel data can be explained by the similar socio-demographic characteristics of the sample families. The correlation disappeared in case of the randomly paired adolescents and young adults. All in all, family background is likely to have a more important impact on fertility desires of youngsters than similar social environment.